2020
DOI: 10.3390/en13174574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additional Xylanase on Saccharification and Ethanol Fermentation of Ammonia-Pretreated Corn Stover and Rice Straw

Abstract: Synergistic effect of cellulase and hemicellulase (xylanase) was evaluated because lignocellulosic material is a heterogeneous complex of cellulose and hemicellulose. Various effects of HTec2 addition on enzymatic saccharification and fermentation were evaluated using two different substrates such as corn stover and rice straw. Corn stover and rice straw were pretreated by the LMAA (low-moisture anhydrous ammonia) method at the preselected same conditions (90 °C, 120 h, moisture content = 50%, NH3 loading = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This finding implied that the SScF utilizing recombinant E. coli (K011) yielded more than 100% of the predicted maximal ethanol production based only on glucan. The results indicated that recombinant E. coli (K011) would efficiently consume glucose and xylose and convert them to ethanol [ 137 ].…”
Section: Fermentation Processmentioning
confidence: 99%
“…This finding implied that the SScF utilizing recombinant E. coli (K011) yielded more than 100% of the predicted maximal ethanol production based only on glucan. The results indicated that recombinant E. coli (K011) would efficiently consume glucose and xylose and convert them to ethanol [ 137 ].…”
Section: Fermentation Processmentioning
confidence: 99%
“…Among them, endo-xylanase, and exo-xylanase are the most important contributors to xylan depolymerization. Until now, vast applications of xylanase have been extensively explored based on its ability in xylan degradation, for example, biofuels production [ 6 , 7 , 8 ], pulp and paper bleaching [ 9 , 10 , 11 ], bioactive compounds [ 12 , 13 , 14 ], animal feed [ 15 , 16 ], and baking [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%